Grassroots petroleum refinery configuration for heavy oil processing - Albahri, T.A. (2019)
This paper presents a model-based optimization approach to design a grassroots petroleum refinery for heavy oil processing including residue treating and upgrading. The focus is to determine an optimal refinery configuration to produce light products from an atmospheric residue stream. The proposed linear model can consider a large number of heavy oil processing technologies (more than 70) including multiple operating modes to arrive at a configuration that meets an objective of maximizing profit or a certain fuel type production. Computational results show trends in agreement with real-world practice for residuum refining applications, thus contributing to substantiating practicality of the approach. Â© 2018, Â© 2018 Taylor & Francis Group, LLC.